DESIGN AND SIMULATION OF A NOISE TO ELECTRICAL ENERGY CONVERTER USING PIEZOELECTRIC TRANSDUCERS - Iliya, Favanza; Augustine Habila, Anuhu; Danladi, Ali (FUDMA Journal of Sciences, 2025)
With global technological advancement and increasing energy demand, especially in developing economies like Nigeria, there is a growing need for sustainable and decentralized micro-power generation systems. Noise energy harvesting offers a renewable approach to supplement conventional electricity supply. This study aims to design and simulate a compact system for converting ambient noise into usable electrical energy using a piezoelectric transduction mechanism. A simulation model was developed in Proteus 8 environment, comprising piezoelectric transducer mesh, Half-Wave Cockcroft–Walton voltage multiplier, control/charging unit, 12V battery and an inverter unit. The mesh generated a peak voltage of 9.5V, which was multiplied to 19V and regulated to a stable 12V for charging a 12V battery. The inverter produced an output power of 1kVA with an estimated efficiency of 82.6%, sufficient to power small home appliances such as laptops, phone chargers and lighting systems. The system exhibited good voltage stability under varying noise intensities, demonstrating its potential as a supplementary renewable energy source. Overall, this study contributes to the development of noise-based micro-power systems suitable for low-energy applications, offering a pathway toward improved energy sustainability and urban renewable integration.